Pengaruh Perilaku Tidak Etis dan Moralitas Individu Terhadap Kecenderungan Fraud Dengan Rasionalisasi Sebagai Variabel Mediasi - Athifanaya Aisya Fatihah; Lisa Kartikasari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to examine the influence of Unethical Behavior and Individual Morality on Fraud Tendency, with Rationalization serving as a mediating variable. The sample consisted of 102 employees working at state-owned banks in Semarang, selected using purposive sampling. The data used in this study consisted of questionnaires distributed according to the research respondent criteria. Data analysis was conducted using SPSS 30.0 software. The results indicate that Unethical Behavior does not have a significant effect on Fraud Tendency, Individual Morality has a significant negative effect on Fraud Tendency, Rationalization has a significant positive effect on Fraud Tendency, Unethical Behavior has a significant positive effect on Rationalization, and Individual Morality does not have a significant effect on Rationalization. The results suggest that Rationalization mediates the relationship between Unethical Behavior and Fraud Tendency but does not mediate the relationship between Individual Morality and Fraud Tendency.